Biopesticide effects on pupae and adult mortality of Anastrepha fraterculus and Ceratitis capitata (Diptera: Tephritidae). Issue 4 (17th August 2017) - Oviedo, Andrea; Van Nieuwenhove, Guido; Van Nieuwenhove, Carina; Rull, Juan
Abstract: Reliance on broad spectrum insecticides for pest control has led to significant environmental damage, human health problems and rapid evolution of insect resistance. These shortcomings have caused a renewed interest in exploring biologically based pest control methods. Among these, the use of plant essential oils, hydrolates and other natural products offer a promising alternative to broad spectrum pesticides. Here, we explored the effect of several bioproducts on pupal and adult mortality (through contact and ingestion) of the two most important pest species of fruit production in South America, South American fruit fly, Anastrepha fraterculus and Medfly, Ceratitis capitata . Topical application of different bioproducts produced different effects on pupal mortality of A. fraterculus and C. capitata . Essential oils of Baccharis dracunculifolia and Pinus elliottii, both containing high proportions of α and β‐pinene and limonene (among other compounds), caused 100% mortality on C. capitata pupae and strongly suppressed adult eclosion of A. fraterculus in comparison with controls. Extracts of Solanum granulosum plus Ricinus communis also caused a moderate yet significant reduction in adult eclosion when compared with the control. All other tested products had no effect on adult emergence. Toxicity on adults through ingestion was greatest for extracts of S. granulosum plus R. communis, followed by Spinosad (Flipper®) and B . dracunculifolia oil (although in these two cases survival was above 40%), while other tested products had no effect on adult mortality. We discuss future research and the potential use of some of the tested products as a component for rational pest management strategies.